Sunny rolls the dice - Holm, Jennifer L (Sunny series, 2019)
"Sunny's just made it to middle school . . . and it's making her life very confusing. All her best friend Deb wants to talk about is fashion, boys, makeup, boys, and being cool. Sunny's not against any of these things, but she also doesn't understand why suddenly everything revolves around them. She's much more comfortable when she's in her basement, playing Dungeons & Dragons with a bunch of new friends. Because when you're swordfighting and spider-slaying, it's hard to worry about whether you look cool or not. Especially when it's your turn to roll the 20-sided die." -- Provided by publisher.